2013
DOI: 10.1242/jcs.134536
|View full text |Cite
|
Sign up to set email alerts
|

Live cell imaging approaches reveal actin cytoskeleton-induced self-association of the actin-bundling protein WLIM1

Abstract: Crosslinking of actin filaments into bundles is critical for the assembly/stabilization of specific cytoskeletal structures. Relatively little is known about the molecular mechanisms underlying actin bundle formation. The two LIM domain-containing (LIM) proteins define a novel and evolutionary-conserved family of actin bundlers whose actin-binding and -crosslinking activities primarily rely on their LIM domains. Using TIRF microscopy, we describe real-time formation of actin bundles induced by tobacco NtWLIM1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 115 publications
(166 reference statements)
1
20
0
Order By: Relevance
“…Zhang et al, 2011b;Bao et al, 2012;van der Honing et al, 2012;Qu et al, 2013), firmly support the notion that plant villins function as a major MF bundling factor in vivo. Our results showed that the bundling frequency was 0.503 310 25 events/µm 2 /s in root epidermal cells (Table 1), which is lower than that in Arabidopsis pollen tubes (2.3 3 10 24 events/ µm 2 /s; Zheng et al, 2013) and hypocotyl epidermal cells (6.9 3 10 25 events/mm 2 /s; Hoffmann et al, 2014), suggesting a possible association between bundling frequency and a cell's growing status. Unexpectedly, inspection of MF dynamics revealed that severing frequency is significantly increased in vln2.…”
Section: Vln2 Possesses Bundling Capping and Severing Activitymentioning
confidence: 57%
“…Zhang et al, 2011b;Bao et al, 2012;van der Honing et al, 2012;Qu et al, 2013), firmly support the notion that plant villins function as a major MF bundling factor in vivo. Our results showed that the bundling frequency was 0.503 310 25 events/µm 2 /s in root epidermal cells (Table 1), which is lower than that in Arabidopsis pollen tubes (2.3 3 10 24 events/ µm 2 /s; Zheng et al, 2013) and hypocotyl epidermal cells (6.9 3 10 25 events/mm 2 /s; Hoffmann et al, 2014), suggesting a possible association between bundling frequency and a cell's growing status. Unexpectedly, inspection of MF dynamics revealed that severing frequency is significantly increased in vln2.…”
Section: Vln2 Possesses Bundling Capping and Severing Activitymentioning
confidence: 57%
“…Deletion of any of the LIM domain reduces affinity to actin, but does not abolish it completely (Thomas et al 2007a). The concrete model of actin bundling has been noticed recently (Hoffmann et al 2014). NtWLIM1 interacts locally with adjoining actin filaments and triggered them to zipper into tight bundles.…”
Section: Ntwlim2mentioning
confidence: 96%
“…Transcriptional regulation (PAL box binding)/lignin biosynthesis Kawaoka et al (2000) NtWLIM1 Actin dynamics Thomas et al (2006Thomas et al ( , 2007a; Hoffmann et al (2014) …”
Section: Ntlim1mentioning
confidence: 99%
See 2 more Smart Citations